A Systematic Literature Review On Customer Retention In The Automobile Or Automotive Industry - Yuly Kridiawan; Gunawan Wang (Cakrawala Repositori IMWI, 2023)
The automotive industry competes fiercely in increasing sales volume between vehicle brands, environmentally friendly vehicles, and social media marketing. The downward trend in profit margins from new car sales has made vehicle distributors pay special attention to the after-sales business, which was proven during the covid-19 pandemic to be a crisis-proof business. After-sales is essential in the automotive industry because customer retention to vehicle dealers contributes to profitability and repurchasing new cars. This research aims to synthesize customer retention in the automotive industry and provide recommendations for future research directions using a systematic literature review approach. A systematic literature review by researching Scopus-indexed journals regarding customer retention in the automobile or automotive industry, followed by bibliometric analysis. The results of this study analyzed Scopus-indexed journals with a total of 1,373 journals published during the last ten years (2014-April 2023). This literature study explains which countries are most active in conducting studies on research subjects, which institutions are the most productive, and which organizations provide a lot of sponsorship funding. This study also reveals what topics are connected to customer retention in the automotive industry and what related issues are currently trending that provide novelty. Researchers can use the findings as a guide for future research, aiming to connect the space between various areas of study in customer relationship management and customer retention in automotive after-sales services. This study found a close relationship between customer retention in the automotive industry and customer relationship management in the after-sales service area.